Achieving near Zero Energy Building in Albania: An Approach for the Retrofit of a Public-School Building - Belussi Lorenzo (EDP Sciences, 2021)
Since its introduction in 2010, the nearly Zero Energy Building (nZEB) concept has known a large diffusion in European countries. Albania, an aspiring candidate country to join the European Union EU, is paving the way towards its introduction by transposing EU directives in the fields of energy efficiency into the national legislation. Most of the national building stock includes buildings with low thermal and energy performance but with high refurbishment potential, too. The country can become an important contributor in the EU decarbonization strategy due to the high percentage of electricity produced by hydropower stations, making it one of the least carbon-intensity countries in the electricity production point of view. The article focuses on the evaluation of the energy performance of an existing school located in Tirana and the potentialities to reach the nZEB target, analysing both the suitable technological solutions and the energy market situation. The Primary Energy Factors PEF for the local electricity market are estimated referring to statistical data and in comparison, with neighbouring countries, Italy and Greece, in order to investigate the potential of the achievement of the nZEB target in Albania.